2007
DOI: 10.1186/1477-7819-5-65
|View full text |Cite
|
Sign up to set email alerts
|

PET probe-guided surgery: applications and clinical protocol

Abstract: The use of the PET probe improves the success of surgical exploration in selected indications. Separate day protocol is clinically feasible allowing for flexible operating room scheduling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 11 publications
1
55
0
1
Order By: Relevance
“…In the last few years, hand-held devices for both PET and SPECT have been developed and used for intraoperative applications (137,433), and in both cases have proven successful in guiding excisions of various tumors. Van Haren and Fitzgerald (433) reported that [ 111 In]-DPTA-octreotide in combination with an intraoperative hand-held gamma camera device helped identify a nonfunctional neuroendocrine tumor that other techniques, including a CT scan and intraoperative investigation, failed to locate.…”
Section: Figure 5 Small Animal Positron Emission Tomography (Pet)mentioning
confidence: 99%
“…In the last few years, hand-held devices for both PET and SPECT have been developed and used for intraoperative applications (137,433), and in both cases have proven successful in guiding excisions of various tumors. Van Haren and Fitzgerald (433) reported that [ 111 In]-DPTA-octreotide in combination with an intraoperative hand-held gamma camera device helped identify a nonfunctional neuroendocrine tumor that other techniques, including a CT scan and intraoperative investigation, failed to locate.…”
Section: Figure 5 Small Animal Positron Emission Tomography (Pet)mentioning
confidence: 99%
“…Tumor-to-non-tumor and tumor-toorgan ratios are higher for delayed images than for the 1.5-hour routine images, and lesion detection is improved in nodal and hepatic metastases (20). Satisfactory count rates and TBR for surgical detection can be obtained 2-4 hours post-FDG administration, which makes this technique clinically feasible (13).…”
Section: Methodsmentioning
confidence: 87%
“…Data suggest that TBR improves over time up to 4 hours post-FDG administration (13). FDG metabolism and clearance occurs at a much faster rate in normal tissues than tumor tissue, and thus TBR improves with time, resulting in better lesion detection when imaging is delayed (19).…”
Section: Methodsmentioning
confidence: 89%
See 1 more Smart Citation
“…This may be difficult in case of prior surgery or chemo-or radiation therapy. To overcome this limitation, we propose to use a sensor that is small enough to be used during operations [1], while being sensitive to the same radioactive tracers utilised in PET scans [2]. This limits the radioactive dose to which the patient is exposed, to the amount required for a PET scan.…”
Section: Introductionmentioning
confidence: 99%